Behavioral effects of antiepileptic drugs in rats: Are the effects on mood and behavior detectable in open-field test?. (November 2017) - Zimcikova, Eva; Simko, Julius; Karesova, Iva; Kremlacek, Jan; Malakova, Jana
Highlights: Antiepileptic drugs (AEDs) are often associated with behavioral side effects. Animal models can help to predict the impact of AEDs on mood, anxiety and depression. Open-field test was used to evaluate drug-related effects on animal behavior. The difficulties faced in interpreting behavioral patterns were demonstrated. Abstract: Purpose: Behavioral side effects of antiepileptic drugs (AEDs) are common including both positive and negative effects on mood, anxiety, depression, and psychosis. We aimed to evaluate behavioral patterns in rats after administration of lamotrigine, levetiracetam, phenytoin, topiramate, carbamazepine, gabapentin, pregabalin, and zonisamide. Methods: The open-field test was performed and locomotion, rearing, grooming, central latency and defecation were recorded over a 5 min interval for each rat (8 rats in each group receiving AED and 16 controls). Kruskal-Wallis nonparametric test or ANOVA were used to assess differences among the groups. Results: The experimental groups did not differ in latency to enter the center compartment, neither in the decline of locomotor activity in the 1st and the 5th minute of the observation, nor in number of rears. Significant differences among groups were observed in the total number of lines crossed, grooming, as well in the number of fecal pellets. Locomotor activity was significantly increased in lamotrigine, if compared with gabapentin and pregabalin (ANOVA; p < 0.05). Rats exposed to topiramate displayed a significantly increased number of grooming (when compared to pregabalin: p < 0.01). Defecation (the number of fecal pellets) significantly increased in the gabapentin and carbamazepine group. Conclusion: There are significant differences between AEDs in terms of their behavioral profile. It is of great importance to evaluate these effects in clinical practice to bring more clear insight into these positive or negative side effects of AEDs.